AKTIVITAS ANTIOKSIDAN EKTRAK METANOL DAN AIR TEH HERBAL POKAK ( Solanum torvum ) TERHADAP ANTIBAKTERI PATOGEN - Nunuk Helilusiatiningsih (BUANA SAINS, 2020)
Pokak (Solanum torvum) can thrive in Indonesia and had high phytochemical and antioxidant compounds. The aim of this study was to analyze the effect of antioxidant compounds on herbal tea products, namely methanol extract of pokak herbal tea and water extract of pokak herbal tea on the inhibition of the growth of pathogenic bacteria. The herbal tea processing method uses surface response. The measured parameters were the total phenol content, tannins, flavonoids, and antioxidant activity (% DPPH Imbibition) and test for pathogenic bacteria inhibition zone using the disc method. The results showed that the best treatment was pokak green tea water extract containing 93.81% antioxidant activity (% DPPH inhibition), total phenol 55.20 mgGAE/g, tannin content 1.70 mgTAE/g, flavonoid levels 1.78 mgQAE/g. Analysis of pokak green tea water extract at a concentration of 100% had an inhibitory power against pathogenic bacteria E coli 20 mm, 20 mm MRSA, 20 ml Salmonella typhi, 19 mm Streptococcus pneumonia. Pokak green tea water extract can be used as a drink that functions for health in inhibiting the growth of pathogenic bacteria.